2022
DOI: 10.1007/s11033-022-07404-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of mutations in genes related to isoniazid resistance in Mycobacterium tuberculosis clinical isolates from Iran

Abstract: Background The global rise in drug-resistant Mycobacterium tuberculosis ( M.tb ), and especially the significant prevalence of isoniazid (INH)-resistance constitute a significant challenge to global health. Therefore, the present study aimed to investigate mutations in prevalent gene loci—involved in INH-resistance phenotype—among M.tb clinical isolates from southwestern Iran. Methods Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Our results showed that annotations of protein-encoding genes are mainly associated with metabolisms being Amino acids and their derivatives, Energy production and conversion, and lipid metabolism, the most representative. Similar studies in other M. tuberculosis populations also showed a high presence of genes related to energy production and conversion (C), amino acid transport and metabolism (E), and lipid transport and metabolism (I) [72][73][74]. This suggests that these genes are widely conserved to ensure the interactions of M. tuberculosis with its human host, especially in mycobacterial persistence, host pathogens struggle for nutrients and immune recognition.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results showed that annotations of protein-encoding genes are mainly associated with metabolisms being Amino acids and their derivatives, Energy production and conversion, and lipid metabolism, the most representative. Similar studies in other M. tuberculosis populations also showed a high presence of genes related to energy production and conversion (C), amino acid transport and metabolism (E), and lipid transport and metabolism (I) [72][73][74]. This suggests that these genes are widely conserved to ensure the interactions of M. tuberculosis with its human host, especially in mycobacterial persistence, host pathogens struggle for nutrients and immune recognition.…”
Section: Discussionsupporting
confidence: 60%
“…In the case of the first-line drug in Mtb treatment, mutations in the 81-bp rifampicin resistance determining region (RRDR) of the rpoB gene, also known as a hotspot region, have been accurate predictors of rifampicin resistance in many studies [69][70][71]. On the other hand, it has been established that INH resistance, predominantly mediated through loss of catalase-peroxidase activity via mutations in katG, produces high-level resistant strains [18,72,73]. Finally, in ethambutol, most resistance-related genes are located on the embB, embC, and upstream of the embA [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in katG, kasA, inhA, fabG1 genes and the oxyR-ahpC intergenic region are associated with conferring resistance to isoniazid (44,62,63), thus ethA/R mutations are associated with ethionamide resistance (48,64,65). Our results were in concordance with previous studies (44,63,66) due to the higher prevalence of mutations in katG (88.8%). Furthermore, it has been shown that mutations in the ahpC promoter conferred resistance by compensatory mechanism (67,68) like L427P in the katG gene (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations may contribute to the faster emergence of MDR strains and highlight the importance of monitoring these genetic changes to prevent the spread of drug resistance. Likewise, mutations in various genes have been associated with conferring resistance to isoniazid [ 55 , 72 , 73 ] and ethionamide [ 59 , 74 , 75 ]. Our study found a higher prevalence of mutations in the katG gene (88.8%), which is consistent with prior research [ 55 , 73 , 76 ].…”
Section: Discussionmentioning
confidence: 99%